El Excentrico, 1956-06-20 - Garcia, Humberto:::Publisher:::::::::::: (San Jose, California; Garcia Printing, 2023)
June 20, 1956 [20 de junio de 1956]. Ano 6, No. 20. Cover contains a group photo of members of the newly formed social club called, Club Zazaree. The headline reads "Excentrico introduces...Club Zarezee all dolls new Social Club."